Medial temporal lobe epilepsy: gender differences. Issue 5 (16th April 2004) - Janszky, J; Schulz, R; Janszky, I; Ebner, A
Abstract : The present study investigated the gender differences in medial temporal lobe epilepsy (MTLE) with regard to clinical history, seizure semiology, and EEG data. To avoid the influence of pathological and localisation differences, we included only MTLE patients with hippocampal sclerosis. Patients who had long term video EEG recordings with registered seizures and unilateral hippocampal sclerosis proved by high resolution MRI were included. There were 153 patients (86 women and 67 men) who met our inclusion criteria. The mean age of the patients was 33.5 years (range 16–59). The mean age at epilepsy onset was 10.8 years. Although there were more women than men, this difference was not significant (p = 0.15). We found that male patients experienced generalised seizures significantly more often, and isolated auras significantly less often than female patients. Analysing EEG data, we found that a seizure pattern lateralised to the side of the hippocampal sclerosis occurred more often in female patients. In the logistic regression analysis, we found that all three factors were associated independently with gender. Odds ratio (OR) for female gender in patients with generalised seizures was 0.44 (95% confidence interval (95% CI) 0.21 to 0.92; p<0.05). In patients with isolated auras OR for female gender was 2.1 (95% CI 1.1 to 4.2; p<0.05). OR for female gender in patients with lateralised seizure pattern was 8.8 (95% CI 1.8 to 42.7; p<0.01). Men more often had secondarily generalised tonic−clonic seizures, while women had isolated auras and lateralised EEG seizure pattern more often. Our data suggest that the seizure spread is more extended or occurs more frequently in men than in women.